As políticas públicas e o desenvolvimento das comunidades de pescadores e pescadoras no interior de Pernambuco - VASCONCELOS, Gilvânia de Oliveira Silva de (2009)
This study has the objective to analyze the impact of public policies for the fishing sector in the State of Pernambuco, Brazil, from 2003 to 2007. We decided to investigate with specific objectives the ocurrence of public policies in countryside water fishing communities; to identify the existing relation between fishing activities and agriculture in some river communities of Pernambuco countryside, and more specifically in the Municipalities of Catende, Cumaru, Ibimirim, Petrolândia and Jatobá, focusing in this comparison the route of those communities and how they started to practice the fishing activity. Also, the co-existence way of both activities fishing and agriculture. This is an exploratory research in its methodological route, bibliography, internet information, visits to Federal Government, State and Non-Governamental Organizations to know each of their objectives and analyze the documents related to their projects and programs to the researched public. Afterwards we visited communities, we did direct observations, informal chats where we used the Field notebook to record experience in communities, and finally, semi-structured interviews. The researched detected that public policies were in 26 thought or done projects from 2003 to 2007 for the communities which make their living by fishing in countryside Waters. But, its majority is still without social or economical sustainability, the projects were with predetermined time, begining, middle and ending. Those who live on fishing, we caracterized them as craft farmer fishermen, because fishing activity is for some of them a source of income and also feeding, linked to periods of rain, the development of selfconsumer agriculture. So, we came to a conclusion that, in the researched period, there was an advance and great achievements from public policies in the sector for craft fishermen in general, when compared with previous periods before the one chosen for this research. But, public policies for the several productive systems of family and fisherman agriculture are also necessary and yet defective, especially when it is the activity of fishing in countryside waters.